2020
DOI: 10.1038/s41598-020-58780-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-reactive protein is a useful marker to exclude anastomotic leakage after colorectal surgery

Abstract: Anastomotic leakage is a complication of colorectal surgery. c-reactive protein (cRp) is an acutephase marker that can indicate surgical complications. We determined whether serum cRp levels in patients who had undergone colorectal surgery can be used to exclude the presence of anastomotic leakage and allow safe early discharge. We included 90 patients who underwent colorectal surgery with primary anastomosis. Serum cRp levels were measured retrospectively on postoperative days (poDs) 1-7. Patients with anasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 46 publications
1
36
0
1
Order By: Relevance
“…Messias et al reported that postoperative serum CRP levels in patients who undergo colorectal surgery could become a marker for the exclusion of anastomotic leakage [ 25 ]. Additionally, Smith et al reported changes in CRP, WBC count and procalcitonin as potential markers of AL following colorectal surgery [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Messias et al reported that postoperative serum CRP levels in patients who undergo colorectal surgery could become a marker for the exclusion of anastomotic leakage [ 25 ]. Additionally, Smith et al reported changes in CRP, WBC count and procalcitonin as potential markers of AL following colorectal surgery [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hoeller et al ( 23 ) pointed out that CRP had a high predictive value for postoperative surgical site infection after dorsal spondylodesis, with sensitivity of 92.9% and specificity of 78.2%. Messies et al ( 24 ) demonstrated that CRP ≥ 180 mg/L on the 4th day after surgery was an independent risk factor for predicting anastomotic fistula after primary anastomosis in patients with rectal cancer ( P = 0.002), with sensitivity and specificity of 72.3 and 88.9%, respectively. Johnson et al ( 25 ) found that postoperative CRP value was an independent risk factor affecting 1-year tumor-free survival ( P < 0.001) and 1-year overall survival ( P < 0.001) after nephrectomy in patients with local renal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a high BMI or obstructive colon cancer need to be treated more carefully. CRP is a well-known acute-phase biomarker that can indicate surgical complications [26]. It reached a peak level in the plasma after 48 hours.…”
Section: Discussionmentioning
confidence: 99%